Arte, liberación y libertad estética: posibilidades y dificultades de una interpretación hermenéutica de la estética de Schopenhauer - Rojas Valdés, Mitchel Angelo (2023)
This paper aims to address a problem in Schopenhauer’s philosophy, specifically, regarding his aesthetics. The problem in question is to determine if it is possible, as a key to hermeneutic reading, to sustain that art provides a liberation to the subject that has the aesthetic experience, understanding that the liberation refers to a suspension in the existence of all volition and desiderative character of the will. The matter is problematic when considering in detail what the german thinker describes as the will, with all its implications: clarifying the term will, it can be found that, at first sight, there is not really a necessity that allows drawing clear conclusions about the function that art fulfills in a possible liberation of the subject from all volition, while he is immersed in a contemplation of an aesthetic nature. However, here it is proposed to demonstrate that, although there is not at first sight the need to fully affirm that art can reliably free the subject from all volition, it can be found by dealing in detail and in depth with the arguments given by Schopenhauer in the third book of The World as Will and Representation, as well as its complements, plus some global notions of the german author’s total system.